AKTIVITAS ANTIOKSIDAN DAN ANTIBAKTERI EKSTRAK DAUN Jatropha gossypifolia L - Nia Sapitri Pangestu; Nurhamidah Nurhamidah; Elvinawati Elvinawati (ALOTROP, 2017)
This study was conducted to determine the activity of Jatropha gossypifolia L (jarak merah’s) leaf extract as an antioxidant and antibactery against acne causing bacteria (Propionibacterium acnes). To obtain an J. gossypifolia L jarak merah’s leaf extract by maceration using 96% ethanol, and then fractionated with n-hexane and ethyl acetate. Testing of antioxidant activity by DPPH method and antibactery activity test by the paper disc method. Antioxidant activity test has done for ethanol fraction, ethyl acetate fraction and n-hexane fraction, while testing for antibacterial activity performed on fractions active as antioxidant. The test results demonstrate the antioxidant activity of ethyl acetate fraction and the ethanol fraction as a fraction very strong with IC50 value of 22.33 ppm for ethyl acetate fraction and 41.04 ppm for ethanol fraction. Then the fraction of ethyl acetate and ethanol fraction antibactery activity test, the result is known that both factions have the ability to inhibit the growth of bacteria Propionibacterium acnes demonstrated by the inhibition zone is formed. In 1000 ppm is formed diameter of the greatest inhibition zone that is equal to 6 mm for ethyl acetate fraction and 5 mm for ethanol fraction.